Decent work in Portugal 2008–18: from crisis to recovery (Geneva, 2018)
"This report has been prepared following consultations with the Ministry of Labour, Solidarity and Social Security (MTSSS) of Portugal with the objective of reviewing the country’s economic and labour market situation since 2008 and examining future prospects.